Systemic staphylococcus aureus infection mediated by Candida albicans hyphal invasion of mucosal tissue - Schlecht, Lisa Marie; Peters, Brian M.; Krom, Bastiaan P.; Freiberg, Jeffrey A.; Hänsch, Gertrud Maria; Filler, Scott G.; Jabra-Rizk, Mary Ann; Shirtliff, Mark E. (Microbiology, 2015)
Candida albicans and Staphylococcus aureus are often co-isolated in cases of biofilm-associated infections. C. albicans can cause systemic disease through morphological switch from the rounded yeast to the invasive hyphal form. Alternatively, systemic S. aureus infections arise from seeding through breaks in host epithelial layers although many patients have no documented portal of entry. We describe a novel strategy by which S. aureus is able to invade host tissue and disseminate via adherence to the invasive hyphal elements of Candida albicans. In vitro and ex vivo findings demonstrate a specific binding of the staphylococci to the candida hyphal elements. The C. albicans cell wall adhesin Als3p binds to multiple staphylococcal adhesins. Furthermore, Als3p is required for C. albicans to transport S. aureus into the tissue and cause a disseminated infection in an oral co-colonization model. These findings suggest that C. albicans can facilitate the invasion of S. aureus across mucosal barriers, leading to systemic infection in co-colonized patients.